Дефініційний аналіз лексеми «Persuasion» - Веренько, Михайло Михайлович; Veren’ko, M. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено дефініційному аналізу лексеми «persuasion» в англійській мові. Змодельовано дефініційну структуру лексеми, що дало можливість виокремити її домінантний та периферійний складники завдя¬ки корпусному – British National Corpus (BNC), Brigham Young UniversityBritish National Corpus (BUY–BNC) і Corpus Of Contemporary American (COCA) – аналізу іменникових лексем на позначення «persuasion». Наведено показники частотності лексем на позначення «persuasion» у різних жанрах англійської мови. The present paper is a study of the lexeme «persuasion». The actuality of the given paper is determined by the need to develop the study of lexical and functional semantics of linguistic units which verbalize the mentioned concept. The purpose of this research is definitional analysis of the component «persuasion», in the system of language and the structure of discourse. The object of the research are lexical-semantic and functional components of semantic units of LSF «persuasion» in the language system and the structure of discourse. The subject of the research  10 dictionaries and 3 corpora of the English language. The definition and its constituents are determined to reveal their status – dominant and periphery. The quantitative features of the lexemes in different registers (genres) are given thanks to the various corpora: British National Corpus (BNC), Brigham Youth University British National Corpus (BYU–BNC), and Corpus Of Contemporary American (COCA) of the English language.
Definitional analysis of the lexeme «Persuasion»
Keywords: лексема; lexeme; дефініційний аналіз; definition analysis; структура значення; meaning structure